Pengaruh Hidrolisis Asam pada Pembuatan Nanoselulosa dari Swietenia mahagoni - Gultom, Rysa Sonya Reni Paulin; Manurung, Posman; Karo Karo, Pulung; Suciyati, Sri Wahyu (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
The extraction of the mahogany pulp as the main ingredient for the preparation of nanocellulose was carried out using the acid hydrolysis method. Sulfuric acid (H2SO4) was used to hydrolyze the primary constituent and sodium hydroxide (NaOH) was utilized in the delignification process. The purpose of this study is to identify the properties of nanocellulose made from mahogany hardwood on fluctuations in H2SO4 concentrations, particularly on concentration 19, 29, 39, and 45%. A Fourier Transform Infrared (FTIR) spectrophotometer, Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD) were used to analyze the sample product, which is cellulose nanocrystal powder. The XRD results stated that the diameter of the nanocellulose crystal size ranged from 3-6 nm, while the SEM results showed that the sample's morphology resembled a stacked arrangement of stones. Meanwhile, the results of the FTIR indicated that the functional groups produced consisted of hydroxyl, aliphatic, aromatic rings, aryl carbonyls, and pyranose. Based on the tests, the best sample is obtained as a concentration variation of H2SO4 39%, which produces a diameter of 3.6 nm with a crystallinity index as high as 80.48%.